2008
DOI: 10.1007/s00595-007-3587-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of soft polyglycolic acid felt for hemostasis and repair of a lacerated liver: Report of two cases

Abstract: The mainstay of treatment for blunt or sharp liver trauma is conservative in 50%-80% of cases. When surgery is indicated, it is demanding and associated with substantial morbidity and mortality. Felt has been used extensively in cardiothoracic and vascular surgery to seal stitches and exposed surfaces. We describe how we used soft polyglycolic acid (PGA) felt to stop bleeding of a lacerated liver in two patients. To our knowledge, this is the first report of PGA felt being used to repair a lacerated liver. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
7
1
1
Order By: Relevance
“…11,12 A recent report noted its utility for hemostasis in a lacerated liver, and the application of PGA may expand in the future. 13 Although PGA felt may cause postoperative infection, or empyema as organ/space SSI, there was no signifi cant difference in the incidence and type of SSI between the PGA(+) and PGA(−) group in the current study (Table 1). Polyglycolic acid felt is absorbed in vivo after about 15 weeks and its strength diminishes after approximately 4 weeks.…”
Section: Discussioncontrasting
confidence: 65%
“…11,12 A recent report noted its utility for hemostasis in a lacerated liver, and the application of PGA may expand in the future. 13 Although PGA felt may cause postoperative infection, or empyema as organ/space SSI, there was no signifi cant difference in the incidence and type of SSI between the PGA(+) and PGA(−) group in the current study (Table 1). Polyglycolic acid felt is absorbed in vivo after about 15 weeks and its strength diminishes after approximately 4 weeks.…”
Section: Discussioncontrasting
confidence: 65%
“…5,6 Polyethylene glycolic acid (PGA) felt is a soft and fl exible absorbable nonwoven textile, and is widely used for tissue reinforcement. [7][8][9] Its attachment on a tissue is greatest when applied in combination with fi brin glue. We herein report the impact of using soft coagulation followed by the application of PGA felt and fi brin glue to prevent PF after DP.…”
Section: Introductionmentioning
confidence: 99%
“…34 Other reports have shown that fibrin sealants effectively achieved hemostasis following laceration of the liver parenchyma. 35,36 We have also previously reported that sealants promoted the successful transplantation of a lacerated liver. 37 Additionally, fibrin sealants reduced the need for blood transfusion after surgery.…”
Section: Discussionmentioning
confidence: 88%